2020
DOI: 10.3389/fphys.2020.00751
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Synergies and Coherence Networks Reflect Different Modes of Coordination During Walking

Abstract: When walking speed is increased, the frequency ratio between the arm and leg swing switches spontaneously from 2:1 to 1:1. We examined whether these switches are accompanied by changes in functional connectivity between multiple muscles. Subjects walked on a treadmill with their arms swinging along their body while kinematics and surface electromyography (EMG) of 26 bilateral muscles across the body were recorded. Walking speed was varied from very slow to normal. We decomposed EMG envelopes and intermuscular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 78 publications
(104 reference statements)
7
45
0
Order By: Relevance
“…When interpreting the results, it is important to keep in mind that intermuscular coherence during gait can be dependent on certain circumstances, such as age (dos Santos et al 2020) or the frequency ratio between arm and leg swing (Kerkman et al 2020). The latter is found to be dependent on walking speed, where a 1:1 ratio is found during a normal walking speed and a 2:1 ratio during very slow walking (<0.8 m/s) (Wagenaar & Van Emmerik, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When interpreting the results, it is important to keep in mind that intermuscular coherence during gait can be dependent on certain circumstances, such as age (dos Santos et al 2020) or the frequency ratio between arm and leg swing (Kerkman et al 2020). The latter is found to be dependent on walking speed, where a 1:1 ratio is found during a normal walking speed and a 2:1 ratio during very slow walking (<0.8 m/s) (Wagenaar & Van Emmerik, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…2020) or the frequency ratio between arm and leg swing (Kerkman et al . 2020). The latter is found to be dependent on walking speed, where a 1:1 ratio is found during a normal walking speed and a 2:1 ratio during very slow walking (<0.8 m/s) (Wagenaar & Van Emmerik, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The reconstruction accuracy of the extracted synergies was determined by the variability accounted for (VAF), which is the ratio of the sum of squared errors to the total sum of squares computed with respect to the mean [ 7 , 37 , 38 ]. Next to VAF we also determined the synergies’ contribution to the matrix (or Frobenius) norm [ 39 , 40 , 41 ], which revealed comparable results. For the sake of legibility, we here present the conventionally used VAF.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle synergies group together muscles based on the co-variation of EMG amplitude during force generation whereas muscle networks group together muscles based on their common neural input in distinct spectral regions, seen as the co-modulation of EMG frequencies, as assessed through the decomposition of the coherence. Previous studies have shown that muscle synergies and coherence muscle networks are complementary to each other and both necessary to understand neuromuscular motor control [30] [31]. Muscle networks have been studied in healthy individuals during postural tasks [30] [32] as well as gait analysis [31], but not yet in individuals with impaired motor control function such as stroke.…”
mentioning
confidence: 99%
“…Previous studies have shown that muscle synergies and coherence muscle networks are complementary to each other and both necessary to understand neuromuscular motor control [30] [31]. Muscle networks have been studied in healthy individuals during postural tasks [30] [32] as well as gait analysis [31], but not yet in individuals with impaired motor control function such as stroke. Thus, how stroke alters muscle networks remains unknown even though the scientific findings can support a better understanding of the changes in intermuscular coordination as the severity of post-stroke impairment increases.…”
mentioning
confidence: 99%